Abundant antibiotic resistance genes in rhizobiome of the human edible Moringa oleifera medicinal plant - Shami, Ashwag Y.; Abulfaraj, Aala A.; Refai, Mohammed Y.; Barqawi, Aminah A.; Binothman, Najat; Tashkandi, Manal A.; Baeissa, Hanadi M.; Baz, Lina; Abuauf, Haneen W.; Ashy, Ruba A.; Jalal, Rewaa S. (Frontiers in Microbiology, 2022)
Moringa oleifera (or the miracle tree) is a wild plant species widely grown for its seed pods and leaves, and used in traditional herbal medicine. The metagenomic whole genome shotgun sequencing approach was used to characterize antibiotic resistance genes (ARGs) of the rhizobiomes of this wild plant and surrounding bulk soil microbiomes and to figure out the chance and consequences for highly abundant ARGs, e.g., mtrA, golS, soxR, oleC, novA, kdpE, vanRO, parY and rbpA, to horizontally transfer to human gut pathogens via mobile genetic elements (MGEs). The results indicated that abundance of these ARGs, except for golS, was higher in rhizosphere of M. oleifera than that in bulk soil microbiome with no signs of emerging new soil ARGs in either soil type. The most highly abundant metabolic processes of the most abundant ARGs were previously detected in members of phyla Actinobacteria, Proteobacteria, Acidobacteria, Chloroflexi and Firmicutes. These processes refer to three resistance mechanisms namely antibiotic efflux pump, antibiotic target alteration and antibiotic target protection. Antibiotic efflux mechanism included resistance-nodulation-cell division (RND), ATP-binding cassette (ABC), and major facilitator superfamily (MFS) antibiotics pumps as well as the two-component regulatory kdpDE system. Antibiotic target alteration included glycopeptide resistance gene cluster (vanRO), aminocoumarin resistance parY and aminocoumarin self-resistance parY. While, antibiotic target protection mechanism included RbpA bacterial RNA polymerase-binding protein. The study supports the claim of the possible horizontal transfer of these ARGs to human gut and emergence of new multidrug resistant clinical isolates. Thus, careful agricultural practices are required especially for plants used in human nutrition or traditional medicine.